1999
DOI: 10.1007/s001670050118
|View full text |Cite
|
Sign up to set email alerts
|

0.2-Tesla magnetic resonance imaging of internal lesions of the knee joint: a prospective arthroscopically controlled clinical study

Abstract: The results of magnetic resonance imaging (MRI) were compared with those of arthroscopy in a prospective series of 244 patients. A dedicated system for MRI of limbs and peripheral joints--the 0.2-T Artoscan (Esaote, Italy)--was used for imaging knee joint lesions. T1-weighted spin-echo sagittal images, T2-weighted gradient-echo coronal images, and axial views for lesions of the femoropatellar joint were acquired. Paraxial sagittal and oblique coronal views were obtained for imaging of the cruciate ligaments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 9 publications
3
25
0
4
Order By: Relevance
“…Similar study conducted by Singh J P et al [15] showed accuracy of 98.84% with sensitivity of 98.72% and specificity of 98.94%. A study done by Riel et al [16] found similar results with accuracy of 97% and sensitivity and specificity of 98% both. Gupta MK et al [17] conducted identical studies on 40 patients with knee injuries with comparable objectives found accuracy of MRI for ACL tear to be 90% with sensitivity of 91.3% and specificity of 88.2%.…”
Section: Discussionsupporting
confidence: 63%
“…Similar study conducted by Singh J P et al [15] showed accuracy of 98.84% with sensitivity of 98.72% and specificity of 98.94%. A study done by Riel et al [16] found similar results with accuracy of 97% and sensitivity and specificity of 98% both. Gupta MK et al [17] conducted identical studies on 40 patients with knee injuries with comparable objectives found accuracy of MRI for ACL tear to be 90% with sensitivity of 91.3% and specificity of 88.2%.…”
Section: Discussionsupporting
confidence: 63%
“…There have been several comparisons of diagnostic performance of diagnosing meniscal tears, cruciate ligaments, and cartilage lesions between low-field and high-field MRI data [7]- [9] reporting everything from compatible performance to the high-field unit outperforming the low-field unit. There has also been a comparison between lowfield MRI and arthroscopy [10] finding a good correspondence between the two for cruciate ligament and lesion detection in the knee.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] It is noninvasive, fast, can be done on an outpatient basis, and is free of complications. Despite this, magnetic resonance imaging is a new technology, 32 which means that clinical experience is still lacking. Additionally, there are doubts about the accuracy of magnetic resonance imaging and the clinical advantages of this test, since it is still an expensive procedure.…”
mentioning
confidence: 99%